A spatially-restricted Younger Dryas plateau icefield in the Gaick, Scotland: Reconstruction and palaeoclimatic implications. (1st May 2019) - Chandler, Benjamin M.P.; Boston, Clare M.; Lukas, Sven
Abstract: Considerable research has been conducted in Scotland to reconstruct Younger Dryas glaciers and palaeoclimatic conditions, but our understanding remains incomplete. In this contribution, we examine the Gaick, a dissected plateau that extends over ∼520 km 2 in the Central Grampians, Scotland. The extent and style of Younger Dryas glaciation in the Gaick has been repeatedly contested, although a model of extensive plateau icefield glaciation has become generally accepted. This is despite well-documented issues with key elements of the plateau icefield reconstruction. We synthesise the results of recent geomorphological mapping in the Gaick and recognise a distinct morphostratigraphic signature in the upper parts of the western catchments. This differs markedly from sediment-landform associations in other parts of the area, and we argue this provides a strong indication of spatially-restricted Younger Dryas (∼12.9–11.7 ka) glaciation in the Gaick. Our interpretation is independently supported by glacierisation threshold analysis, which implies that the eastern Gaick was unable to nourish Younger Dryas ice. We therefore contest the accepted paradigm of extensive Younger Dryas glaciation in this area. Based on the geomorphological evidence and glacier surface profile modelling, we reconstruct a ∼42 km 2 plateau icefield that yields an equilibrium line altitude of 751 ± 46 m. Using this value, a sea-level precipitation value of 826 ± 331 mm a −1 is inferred for the Younger Dryas, which suggests considerably drier conditions than at present. Using recalculated glacier-derived precipitation estimates from Scotland, we present regional climate analysis that corroborates arguments for a strong west-east precipitation gradient across Scotland. Highlights: Geomorphological mapping reveals evidence for a restricted Younger Dryas icefield. Novel glacierisation threshold analysis independently supports limited plateau ice. The evidence challenges accepted paradigm of extensive plateau icefield glaciation. The spatially-restricted Younger Dryas Gaick Icefield has an ELA of 751 ± 46 m. Strong eastward precipitation decline is indicated by glacier-derived climate data.